Synthesis, characterization and application of 1-butyl-3-methylimidazolium tetrafluoroborate for extractive desulfurization of liquid fuel - Swapnil A. Dharaskar (Arabian Journal of Chemistry, 2016)
In the present paper the experimental data of extractive desulfurization of liquid fuel using 1-butyl-3-methylimidazolium tetrafluoroborate [BMIM]BF4 have been presented. The data of FTIR, 1H NMR and 13C NMR have been discussed for the molecular confirmation of synthesized [BMIM]BF4. Further, the thermal properties, conductivity, solubility, and viscosity analysis of the [BMIM]BF4 were carried out. The effects of reaction time, reaction temperature, sulfur compounds, and recycling of ionic liquid without regeneration on dibenzothiophene removal of liquid fuel were presented. In extractive desulfurization process, the removal of dibenzothiophene in n-dodecane was 73.02% for mass ratio of 1:1 in 30 min at 30 °C under the mild reaction conditions. The ionic liquids could be reused four times without a significant decrease in activity. Also, the desulfurizations of real fuels, multistage extraction were presented. The data and results provided in the present paper explore the significant insights of imidazoled ILs for extractive desulfurization of liquid fuels.